Six-Year Demographic Study of the Terrestrial Orchid, Crepidium acuminatum: Implications for Conservation - Timsina, Binu; Kindlmann, Pavel; Münzbergová, Zuzana; Rokaya, Maan B. (Frontiers in Ecology and Evolution, 2021)
Studies on population dynamics are helpful for understanding the factors determining population development and predicting the effects of disturbances, such as harvesting of plant species. In an investigation of the demography of a terrestrial medicinal orchid known as Crepidium acuminatum, the effects of harvesting on its population dynamics were recorded. Data on recruitment, growth and survival were collected in three populations of C. acuminatum over a 6-year period (2012–2017) in central Nepal. A matrix modelling method was used to determine the effect of different harvesting regimes on the population growth and survival of this species. Population growth rates (λ) of unharvested populations were relatively similar and stable in different years of the study. Harvesting significantly reduced λ. The results of this study indicate that the sustainable survival of a population that is subject to harvesting can only occur when it is either selective (only flowering individuals or only small amounts of vegetative individuals) or rotational (once every 3 to 5 or more years). This study demonstrates the necessity of using a sustainable method when harvesting natural populations. Our results are useful for developing efficient management strategies for this species. As each species has a different biology, similar studies are needed for other rare and/or economically important species in the Himalayan region and in other understudied parts of the world.